Marketing communication strategies for chinese automotive OEMs operating in South Africa: the role of diversity in consumer decision-making - Rosenbaum, Stephen (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.